(untitled) (Stato, Chiese e pluralismo confessionale, 2025)
Ecclesiastical tax law facing European primacy: new reflections from Constitutional Court no. 20 of 2025 Taking as its starting point the recent judgment of the Constitutional Court No. 20 of 2025, this contribution delves into the state of the art of the interactions between national ecclesiastical law (in its tax sector) and European Union competition law. The raising of a question of constitutionality concerning the regulation of the ‘old’ ICI exemption under Article 7(1)(i) of Legislative Decree No. 504 of 1992 provides the Court with an opportunity to reaffirm the special active force of the law implementing the Villa Madama Agreement (Law No. 121 of 1984). In the background of the dispute looms the dutiful recovery of unpaid ICI for the tax years 2006-2011, ordered by the European Commission with Decision of 3 March 2023 (2103/2023/EU) and recently regulated by the national legislator with Decree-Law no. 131 of 2024. Although it did not materialise in the present case, a conflict between the self-executing legislation protecting competition and a favourable discipline derived from concordat law could evoke the spectre of counter-limits to EU law. SOMMARIO: 1. Introduzione. Le ragioni di una (inammissibile) questione di costituzionalità - 2. L’esenzione dai tributi diretti sugli immobili posseduti e utilizzati dagli enti ecclesiastici. La ratio del trattamento fiscale agevolativo - 3. (segue)… e la sua problematica armonizzazione con i principi concorrenziali del mercato interno - 4. Tutela della concorrenza e (apparente) pretermissione della ‘clausola di salvaguardia’ dello status nazionale delle Chiese e dei loro enti (art. 17.1 TFUE) - 5. La Corte costituzionale e l’apparente riaffermazione della special forza attiva delle fonti di diretta derivazione concordataria - 6. Il parametro fondamentale della bilateralità pattizia e lo spettro (implicito) dei controlimiti al diritto eurounitario - 7. Conclusioni.